IMPACT OF COVID-19 PANDEMIC ON PERCEIVED STRESS AND ITS ASSOCIATION WITH HAVING CHILDREN AMONG PHYSICIANS IN SAUDI ARABIA - Alghamdi, Khaled; Abdallah, Ayat Roushdy; Zalat, Marwa Mohamed; El-Sonbaty, Marwa M.; Khan, Adeel Ahmed; Ibrahim, Hanan Mosleh (Journal of Ayub Medical College Abbottabad, 2021)
Background: The global pandemic of COVID-19 has led to unprecedented psychological stress on frontline health professionals. The objective of our study was to determine the prevalence of perceived stress and its association with having children among physicians in Al Madinah city, Saudi Arabia, during the COVID-19 pandemic. Methods: A web-based analytical cross-sectional study was conducted among the physicians working in Al-Madina, Saudi Arabia. Physicians living in Madina city were invited to participate in this survey by using an online questionnaire that consisted of socio-demographic information, and Perceived Stress Scale (PSS) 10 items questionnaire. The outcome measure was perceived stress score and levels among participants, while exposure factors were having children and the number of children of each participant. Results: Low, moderate and high levels of perceived stress were found in 39.3%, 56.4% and 4.3% of the physicians, respectively. 53.6% of those physicians who have children, had significant moderate perceived stress as compared to 93.3% of those who do not have any children (odds ratio (OR) = 0.08, 95% confidence interval (CI) 0.01-0.65, p=0.004). There was an inversed significant correlation between the number of children a participant had and the perceived stress scale score (R = ˆ’0.21, p=0.026). Conclusion: COVID-19 pandemic resulted in perceived stress among physicians in Saudi Arabia, mostly moderate level. Having children was found to be a protective factor.